Efeitos in vitro da triiodotironina na diferenciação condrogênica das células-tronco mesenquimais da medula óssea de ratas - Assis, Higor Azevedo (2017)
Bone marrow mesenchymal stem cells (BMMSCs) are cells with chondrogenic differentiation capacity that have receptors for thyroid hormones. The aim of the present study was to verify the in vitro effect of triiodothyronine (T3) on the chondrogenic differentiation of female rat BMMSCs over several time periods and at several doses. CD54+/CD73+/CD90+ BMMSCs from Wistar female rats were cultured in chondrogenic medium with or without T3 and were separated into five groups: 1) BMMSCs without T3; 2) BMMSCs with 0.01 nM T3; 3) BMMSCs with 1 nM T3; 4) BMMSCs with 100 nM T3; and 5) BMMSCs with 1,000 nM T3. At seven, 14, and 21 days, the cell morphology, chondrogenic matrix formation, and expression of Sox9 and collagen II were evaluated. For the analyses, the Kruskal-Wallis test was used, followed by the Dunn post hoc test or the Student-Newman-Keuls test. The dose of 100 nM did not alter the parameters evaluated in any of the periods studied. However, the 0.01 nM T3 dose improved the chondrogenic potential by increasing the chondrogenic matrix formation and expression of Sox9 and collagen II in at least one of the evaluated periods; the 1 nM T3 dose also improved the chondrogenic potential by increasing the chondrogenic matrix formation and the expression of collagen II in at least one of the evaluated periods. The 1,000 nM T3 dose stimulated early cell hypertrophy but improved the chondrogenic potential by increasing the chondrogenic matrix formation and Sox9 expression in at least one of the evaluated periods. In conclusion, T3 has a dose-dependent effect on the differentiation of BMMSCs from female rats. Here, 0.01 nM T3 was the dose that presented the best effect by increasing the chondrogenic matrix formation and the expression of Sox9 and collagen II in at least one of the evaluated periods.